2002
DOI: 10.3171/jns.2002.96.3.0527
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcome in surgically managed patients with typical and atypical trigeminal neuralgia: comparison of results following microvascular decompression

Abstract: In this study, MVD for typical TN resulted in complete postoperative pain relief in 80% of patients, compared with 47% with complete relief in those with atypical TN. Significant pain relief was achieved after 97% of MVDs in patients with typical TN and after 87% of these procedures for atypical TN. When patients were followed for more than 5 years, the long-term pain relief after MVD for those with typical TN was excellent in 73% and good in an additional 7%, for an overall significant pain relief in 80% of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
3
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(117 citation statements)
references
References 9 publications
(8 reference statements)
7
100
3
7
Order By: Relevance
“…1,17 In considering MVD for TN, the utility of distinguishing between the various subtypes of TN is becoming clearer. In reviewing Jannetta's 7 results over a 24-year period, Tyler-Kabara et al 23 have shown that patients with typical TN fare far better than those with atypical TN. Li et al 10 have suggested that patients with typical TN of a shorter duration fare better following MVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,17 In considering MVD for TN, the utility of distinguishing between the various subtypes of TN is becoming clearer. In reviewing Jannetta's 7 results over a 24-year period, Tyler-Kabara et al 23 have shown that patients with typical TN fare far better than those with atypical TN. Li et al 10 have suggested that patients with typical TN of a shorter duration fare better following MVD.…”
Section: Discussionmentioning
confidence: 99%
“…2,20 Recently, some authors have proposed the term "transitional TN." 23 While many cases of TN do transition from strictly typical to atypical TN, 2 others begin with constant background pain (usually "burning") with crescendos or paroxysms of lancinating pain throughout the day and do not fit this transitional subgroup. Most recently, in response to Heros,6 Burchiel wrote, "Type 2 TN may well be a composite category, containing one or more other diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Other features identified as associated with improved long-term outcome include memorable onset, trigger points, lack of sensory loss, 14 shorter preoperative duration of pain, 1,12 single artery compression, and complete arterial decompression. 12 To our knowledge, no investigators have yet evaluated pain-free intervals or response to AEDs, nor has any study systematically examined the relative impact of each of these in a single patient population.…”
Section: 14mentioning
confidence: 99%
“…Although the period of follow up was not long enough, most surpass two years, whereas in the literature most recurrences of TN after MVD occurred in the first two years after operation (2,7,21,23,25), the recurrence rate decreased thereafter, and so there was conviction of our data in certain degree. Why did MVD+PSR improve the surgical outcomes?…”
Section: Surgical Findingsmentioning
confidence: 64%
“…To date, various surgical procedures for treatment of TN have been applied, such as percutaneous balloon microcompression (PBC) (14,22), radiofrequency thermorhizotomy (RTR) (10,16), partial sensory rhizotomy (PSR) (11,27), and microvascular decompression (MVD) (7,21,25). Unfortunately, there is no ideal surgical procedure could immediately and completely relieve this intolerable pain, eliminate all needs for medications, let alone no recurrence of TN.…”
Section: Introductionmentioning
confidence: 99%